Injustice in Urban Sustainability - Kotsila, Panagiota; Anguelovski, Isabelle; García-Lamarca, Melissa; Sekulova, Filka (Taylor & Francis, 2022)
This book uses a unique typology of ten core drivers of injustice to explore and question common assumptions around what urban sustainability means, how it can be implemented, and how it is manifested in or driven by urban interventions that hinge on claims of sustainability.